Greening the career incentive structure for local officials in China: Does less pollution increase the chances of promotion for Chinese local leaders? - Wu, Mingqin; Cao, Xun (Journal of environmental economics and management, 2021)
Does it pay to be “greener” as a local official in China? In this paper, we examine the effect of local environment regulation outcomes, i.e., local pollution, on leaders’ chances of promotion. This is an important question because only when the Chinese cadre evaluation system rewards local officials’ green behaviors, these officials would move away from their past priority in promoting economic growth at all costs, so that the environmental crisis in China might be addressed. We collect party secretary data for Chinese counties between 2001 and 2014 to measure promotion patterns. We construct county-year SO2 and PM2.5 pollution measures using NASA satellite data. We adopt an instrumental variable approach to deal with potential endogeneity issues of the pollution variables: for both PM 2.5 and SO2, we use ventilation coefficient, i.e., the product of wind speed and mixing layer height, as the instrument. Our empirical analysis shows that for county party secretaries, those who are able to reduce air pollution are more likely to be promoted. We find similar results for county magistrates. However, we do not find evidence for this pollution-promotion link for prefecture and provincial party secretaries.